Anti-Microorganism Activity of Chitosan and Nano-Silicon Dioxide Mixture on Damage Causing Strains Isolated from Postharvest Guava - Dien T.V. To; Pam T.H. Van; Le S. Ngoc; Them T. Le; Huy C. T. Phan; Tran D. Manh (Chemical Engineering Transactions, 2022)
Postharvest decay of guava is mainly caused by microorganism species during storage time. Therefore fungal and bacterial species that may cause decay on postharvest guava were isolated and evaluated the antimicrobial and antifungal ability by Low-molecular-weight (LMW) chitosan in combination with nano-silicon dioxide (nano SiO2) compound was carried out. The study successfully isolated four fungal species, namely Chrysosporium tropicum, Cladosporium sphaerospermum, Aspergillus wentii, Colletotrichum acutatum and three bacterial species, namely Azotobacter sp., Escherichia coli, Bacillus subtilis, which is most likely to cause decay on postharvest guava. It is found that a mixture of 0.04% nano SiO2 and 1% Low-molecular-weight chitosan 44.5 kDa are capable confront microorganism tested with the highest antibacterial zone diameter and the lowest diameter of growing fungi. This work contributes the potential compound for prolonging shelf-life of postharvest guava.